The problem of coca in Peru - Monge, Carlos (1946)
Much has been written and very little research has been done on the "coking" in antiplanos of America. For some it is "sacred ground" that affirms life at altitude; for others, it causes degeneration of the race. The Institute of Andean Biology deals today for this problem approaching it with a strictly scientific criteria